MONEY ATTITUDE AND FINANCIAL BEHAVIOR TO SUPPORT THE FINANCIAL WELL-BEING OF SMES IN WEST SUMATRA - Anggraini, Fivi; Wahyuni, Nengsih Sri; Yunilma; Nurhuda (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
Financial well-being plays a crucial role in the sustainability of small and medium enterprises (SMEs). As such, it is considered one of the key factors supporting business continuity in Indonesia, particularly in West Sumatra. The concepts of money attitude and financial behavior are critical for SME owners in enhancing their financial well-being. Financial well-being can serve as an effective strategy for improving financial stability in the development of SMEs. This study aims to empirically examine the impact of money attitude on financial well-being, with financial behavior acting as a mediating variable. A purposive sampling method was employed, involving 178 SMEs operating in West Sumatra as respondents. Data were collected through a survey, where questionnaires were distributed directly to SMEs at their business locations, as well as via Google Forms for areas difficult to access by the researchers. The data analysis technique used was Partial Least Squares (PLS) version 3.0. The findings indicate that money attitude significantly influences financial well-being, with financial behavior mediating this relationship.